Immunoglobulin G (IgG) Anti-Tissue Transglutaminase Antibodies Used as Markers for IgA-Deficient Celiac Disease Patients - Dahlbom, Ingrid (American Society for Microbiology, 2005)
The role of immunoglobulin A (IgA) anti-tissue transglutaminase antibodies (IgA-tTG) as predictors of untreated celiac disease (CoD) is well documented, and the presence and levels of these antibodies are most accurately monitored with native or recombinant human antigens. However, IgA-deficient CoD patients are not identified by IgA serology, and conflicting results concerning the diagnostic validity of IgG antibodies against gliadin (IgG-AGA), endomysium (IgG-EmA), and tTG (IgG-tTG) have been reported. The aim of the present study was to evaluate the utility of IgG-tTG for the detection of CoD in IgA-deficient patients. Samples from 115 IgA-deficient and 200 IgA-sufficient subjects were collected and tested for the presence of IgA and IgG antibodies against tTG, EmA, and AGA. Antibodies against tTG were measured by an enzyme-linked immunosorbent assay based on recombinant human tTG, and antibodies against EmA were determined by immunofluorescence. The values for IgG-tTG showed a higher correlation (correlation coefficient [r] = 0.91) with those for IgG-EmA for the IgA-deficient subjects than for the IgA-sufficient subjects (r = 0.88). The overall concordance of the positive and negative results between IgG-tTG and IgG-EmA was 97%, and the IgG-tTG assay discriminated between IgG-EmA-positive and -negative subjects with IgA deficiency at a rate of 100%. Elevated levels of IgG-tTG and IgG-EmA were measured in 70% of the IgA-sufficient subjects. IgG-tTG detection with recombinant human tTG is a good alternative to IgG-EmA detection, and the addition of IgG-tTG assessment to present screening methods may improve the ability to identify IgA-deficient subjects with CoD.